Sydskandinavisk i Nordskandinavien - Simonsen, Povl (Kuml, 1970)
South-Scandinavian petroglyphic art in northern Scandinavia It has long been considered that the rock-carvings of southern Scandinavia have been connected with agriculture. One of the arguments for this was that both phenomena had about the same northern limit, c. 66° N. In the last 15 years, however, a number of finds of southern Scandinavian type have been found further north, as far as 703⁄4° N or almost to the North Cape. Published here are a female figure from Isnestoften, 2 boat pictures from Gåshopen and 2 rocks with cup-marks. We also encounter south-Scandinavian traits in the Arctic petroglyphs, which are attributed to the hunting population of northern Scandinavia. The conclusion is that the two stages coalesce in their culminating phases, both stylistically and geographically. »South Scandinavian« elements can after 500 B.C. not be considered to have any clear connection with a peasant population. P. Simonsen